Implicit meanings : selected essays in anthropology - Douglas, Mary (Routledge, 1999)
Implicit Meanings was first published to great acclaim in 1975. It includes writings on the key themes which are associated with Mary Douglas' work and which have had a major influence on anthropological thought, such as food, pollution, risk, animals and myth. The papers in this text demonstrate the importance of seeking to understand beliefs and practices that are implicit and a priori within what might seem to be alien cultures.